2016
DOI: 10.1016/j.jand.2016.07.016
|View full text |Cite
|
Sign up to set email alerts
|

“Great Job Cleaning Your Plate Today!” Determinants of Child-Care Providers’ Use of Controlling Feeding Practices: An Exploratory Examination

Abstract: Training providers about negative child outcomes associated with CFP, children's ability to self-regulate energy intake, and differentiating between controlling and healthful feeding strategies may help providers to avoid CFP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 41 publications
2
28
1
Order By: Relevance
“…Previous qualitative work among ECETs’ uncovered that controlling feeding practices such as pressuring children are thought to be effective to get children to eat the right amount. 61 This study’s findings support the perceived efficacy of these unsupportive practices and further highlight motivations for their use.…”
Section: Discussionsupporting
confidence: 65%
“…Previous qualitative work among ECETs’ uncovered that controlling feeding practices such as pressuring children are thought to be effective to get children to eat the right amount. 61 This study’s findings support the perceived efficacy of these unsupportive practices and further highlight motivations for their use.…”
Section: Discussionsupporting
confidence: 65%
“…Concern over ensuring that children eat enough, as expressed by parents in this study, has been found to impact provider practices in child care settings. 22,42 One study conducted with child care providers found that fear of negative parental response to children not eating in child care was a barrier to communicating effectively with parents, and implementing practices that encourage healthy eating behaviors in young children. 42 These finding align with the SEM, 35 and support the home-daycare link model that suggests caregiver-parent relationships and interactions are reciprocal and contribute to a continuity of care (consistency) across both environments.…”
Section: Domain Ii: Awareness Of the Fcch Nutrition And Food Environmentmentioning
confidence: 99%
“…22,42 One study conducted with child care providers found that fear of negative parental response to children not eating in child care was a barrier to communicating effectively with parents, and implementing practices that encourage healthy eating behaviors in young children. 42 These finding align with the SEM, 35 and support the home-daycare link model that suggests caregiver-parent relationships and interactions are reciprocal and contribute to a continuity of care (consistency) across both environments. 23 Strategies to increase the frequency of parent-FCCP child nutrition related communication need to take into consideration the context of parents' daily life demands.…”
Section: Domain Ii: Awareness Of the Fcch Nutrition And Food Environmentmentioning
confidence: 99%
“…50 Children's food refusal leads providers to use controlling feeding practices as a straightforward approach to encourage preschoolers to try new foods and eat fruits and vegetables. 48,50,51 Unfortunately, such practices are a risk factor for poor eating habits and childhood obesity. 52,53 In addition to the aforementioned challenges to mealtime NE, lack of availability of nutritious foods and beverages at mealtime 54 and provider nutrition knowledge 37 may attenuate the quality of NE at mealtime and fail to influence children's eating behaviors.…”
Section: Discussionmentioning
confidence: 99%